ANALYSIS REJECT MEASURE IN TESTING NON CONSTITUTIONAL LAW ON THE CONSTITUTION NRI 1945 - Baharudin Baharudin; . Tantolailam; T T (International Conference On Law, Business and Governance (ICon-LBG), 2016)
Research shows that there are the premise of allowing the use of non constitution of the deision of the court, namely. First the Constitution Court in examining the legislation required to explore the values of law and justice in the society based NRI Constitution of 1945, as the bighest legal basis and the law as the elaboration of the Constitution NRI 1945. The use of the of the law concerning the establishment of laws and the order of the haose of representatives as the basis for the Court’s decision in interpreted as the elaboration of the Constitution directly NRI 1945.The second practice of the Constitutional Court in the previous decicionNamber 27/PUU/VII/ 2009, dated June 16. 2010 among other things sateted “…. Along Act Rules agency products, and legislation governing formal procedural macanism or the flowing of a delegation of authority under the constitution, the laws and undanagn it can be used or considered as a measure or touchstone of the formal review. Third, the use of any other law as the basis of legal caonsiderations rather to create legal certainty as specified in Article 28 D paragraph (1) Constitution NRI 1945.Fourth, the prohibition of using any other law as the basis of legal consideretions is to reduce the authority of the court as an independent judicial to organize judicial administration to ubold the law and justice.Terms non constitution as benchmarks, including : First, non constitution norm is a norm NRI delegates from the Constitution of 1945, two non-constitutional substance is a subtstance or material that shold be regulated by law, As the third norm executor of the process of ofebtablishing laws.